Behaviour of N\(_2\) Active Species in Microwave Plasma and Early Afterglows at Low Pressure - Julio Henriques; André Ricard (Plasmas Afterglows with N2 for Surface Treatments synthesis 2024, 2025)
The excited states in N2 plasma and flowing afterglows at reduced pressure are studied for the plasmas and for the afterglows. The N2 flowing microwave discharges have been investigated by emission spectroscopy in the following conditions: N2 at p = 5 Torr, flow rate of 0.3 slpm, t = 1.5×10-3 s and microwave power of P = 150 W. Two experimental setups were analyzed: one with the plasma (produced inside a 5 mm ext. dia. tube) directly connected to a larger post-discharge tube (with a diameter of 15 mm) and another with the introduction of an Ar-NOext mixture after the plasma in the small tube. Under these conditions, the production of N2+ ions in the plasma and in the early afterglow is done predominantly by electron collisions. After the end of the plasma up to the pink afterglow, N2(A) and N2(X,v>11) were the excited species at the origin of the N2(C) and N2+(B) emissions. A self-consistent theoretical model was introduced to explain the production of the N2 active species by particle kinetics. The intensity ratio I\(N_2^+(B)\)/I\(N_2(C)\) increased 15 times from the plasma to the pink afterglow. In this setup, the gas temperature was about 1000 K in the plasma and 700 K in the pink afterglow. In a second setup, the plasma end was at 12 cm of the post-discharge tube. The gas temperature was lower: 750 K at 2 cm and 400 K at the plasma end (3.5 cm). The effect of adding an Ar-NOext gas mixture (used for N-atom titration in the late afterglow inside the 15 mm diameter tube) at the discharge end was studied along the 5 mm diameter tube. It was concluded first that the destruction of N-atoms by NOext decreased the intensity of the N(2P) and N2(B) radiative states. Second, the electrons at the plasma end could excite the N2(C) and N2+(B) radiative states. It was revealed that the destruction of N-atoms caused by the addition of NOext also produced a decrease in the intensities of the N(4P) and N2(B) radiative states. The plasma electrons were still influential in the excitation of the N2(C) and N2+(B) radiative states after the plasma end.